STUDENT’S DIFFICULTIES IN LISTENING TOEIC TEST OF SEMESTER II (MECHANICAL ENGINEERING STUDENTS) AT THE STATE POLYTECHNIC BENGKALIS - Desi Wahana; Ari Satria; Safra Apriani Zahraa (INOVISH JOURNAL, 2023)
Toeic test is one of the requirements to graduate at State Polytechnic Bengkalis. To pass in Toeic test, some of students get difficulties to pass the passing grade. The aim of this study is to find out students’ difficulties in listening to Toeic tests and how to overcome the problem. This study found that students’ ability in listening comprehension on Toeic test was average category from 11 students by 36.7%. Then students ‘difficulties in Toeic tests Picture description (used similar sound answered agree by 50%), question response (the speech rate answered agree by 53.3%), short conversation (unfamiliar word answered strongly agree by 53.5%), short talks (can easily miss the text answered agree by 43.3%).